Pandangan Gembala dan Penatua GSJA Sipoholon Tentang Allah Yang Cemburu dan Pembalas Berbasis Nahum 1:2-4 - Rimma Tahi Nauli Simamora; Iwan Setiawan Tarigan (Jurnal Pendidikan Agama dan Teologi, 2023)
Nahum 1:2-4 contains statements about God's character that are found in the Torah, the Hebrew Bible section. This is a quote from the Book of the Prophet Nahum, in which Nahum conveys God's message to the Assyrians. God is jealous and avenger because of His hatred of the wickedness of the Assyrians. GSJA Sipoholon responds that God is jealous, not like jealous humans, but He deserves that glory because He is the center of all truth that deserves our respect because He is the source of all things. The research method used is a qualitative qualitative method in which the author conducts field observations and interviews with GSJA Sipoholon sources regarding the views of the Pastors and Elders about "The Jealous and Avenging God". The results of the research are that God is jealous and avenger because the Assyrians are full of evil.